Therapeutic Potential of Human Induced Pluripotent Stem Cells in Experimental Stroke. Issue 8 (August 2013) - Chang, Da-Jeong; Lee, Nayeon; Park, In-Hyun; Choi, Chunggab; Jeon, Iksoo; Kwon, Jihye; Oh, Seung-Hun; Shin, Dong Ah; Do, Jeong Tae; Lee, Dong Ryul; Lee, Hyunseung; Hong, Kwan Soo; et al.
Ischemic stroke mainly caused by middle cerebral artery occlusion (MCAo) is a major type of stroke, but there are currently very limited therapeutic options for its cure. Neural stem cells (NSCs) or neural precursor cells (NPCs) derived from various sources are known to survive and improve neurological functions when they are engrafted in animal models of stroke. Induced pluripotent stem cells (iPSCs) generated from somatic cells of patients are novel cells that promise the autologous cell therapy for stroke. In this study, we successfully differentiated iPSCs derived from human fibroblasts into NPCs and found their robust therapeutic potential in a rodent MCAo stroke model. We observed the significant graft-induced behavioral recovery, as well as extensive neural tissue formation. Animal MRI results indicated that the majority of contralaterally transplanted iPSC-derived NPCs migrated to the peri-infarct area, showing a pathotropism critical for tissue recovery. The transplanted animals exhibited the significant reduction of stroke-induced inflammatory response, gliosis and apoptosis, and the contribution to the endogenous neurogenesis. Our results demonstrate that iPSC-derived NPCs are effective cells for the treatment of stroke.